A Mini-Review of Digital Technologies (IoT, AI) for Enhancing Sustainability Monitoring in Indonesian Agriculture and Forestry - Eny Fahrati; Thiago Rocha; Lucas Lima (Yayasan Adra Karima Hubbi, 2025)
Background. The integration of digital technologies such as the Internet of Things (IoT) and Artificial Intelligence (AI) into agriculture and forestry holds great potential for enhancing sustainability monitoring, especially in Indonesia, where these sectors are crucial to the economy and environment. Purpose. The challenges of climate change, deforestation, and inefficient resource use have led to the need for advanced technologies to better manage natural resources and monitor sustainability in these sectors. This mini-review aims to assess the role of IoT and AI in improving sustainability monitoring in Indonesian agriculture and forestry, exploring the benefits, challenges, and future prospects. Method. A comprehensive review of existing literature, case studies, and reports was conducted to gather data on the applications of IoT and AI in agriculture and forestry in Indonesia. The research examines the current technologies being implemented, their impact on resource efficiency, and the potential for scalability and integration into existing systems. Results. The findings indicate that IoT-based sensors and AI-driven analytics have significantly improved data collection and decision-making processes, enabling better management of water, soil, and forest resources. However, challenges such as infrastructure limitations, data privacy concerns, and the need for skilled labor remain. Conclusion. In conclusion, digital technologies such as IoT and AI offer promising solutions for enhancing sustainability monitoring in Indonesia’s agriculture and forestry sectors. While progress is being made, there is a need for further investment in infrastructure, capacity building, and policy development to maximize the impact of these technologies.